Environmental innovation and financial performance: Mediating role of environmental management accounting and firm's environmental strategy - Naveed Iqbal Chaudhry; Humaira Asad; Muhammad Amir Ch.; Rai Imitiaz Hussain (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
The purpose of this study is to empirically investigate the impact of environmental innovation constituting product innovation (PDI) and process innovation (PCI) on firms' financial performance (FFP). It also inquires the mediating roles of environmental management accounting (EMA) and the firm's environmental strategy (FES) between innovation and FFP. We have analyzed primary data collected from 363 respondents, working at the managing positions in the manufacturing sector of Pakistan. The proposed model was estimated by applying structural equation modeling. Results show that PDI and PCI have positive and significant impacts on FFP. Furthermore, the findings indicate that EMA and FES mediate the relationship between innovation and FFP in the manufacturing sector of Pakistan. This is the first study in the available literature on EMA, which promulgates a comprehensive theoretical model in the context of the manufacturing sector of Pakistan by introducing two mediators between the association of environmental innovation and firms' financial performance. This study suggests the managers of the manufacturing companies or similar sectors to introduce innovations in their products and processes for developing a better EMA system; they must propose appropriate environmental strategies to enhance their firms' performance. The current study also tends to assist policymakers in developing appropriate policies for the manufacturing sector of Pakistan by realizing the importance of environmental innovation, EMA, and FES so that their environmental and economic impacts can be managed and regulated.
Keywords: 330; environmental innovation; product innovation; process innovation; financial performance; environmental management accounting; firm's environmental strategy; manufacturing sector; Pakistan